Comparison Of Remote And Self-Positioning Approaches For Indoor Ble-Based Localization - Rozum, Stanislav (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
This paper deals with Received Signal Strength (RSS) positioning based on BluetoothLow Energy technology. Specifically, it compares two concepts, remote and self-positioning, usingtheir design properties and the RSS maps. The fundamental difference between both modes lies inunits’ tasks with the known and unknown positions. In our experiment, the fixed units - anchorsexploit multiple antennas, whereas the movable device uses a classic single antenna. The system canoperate in either mode, thus eliminating the influence of different hardware.
Keywords: remote-positioning; self-positioning; BLE; localization; RSS